The self-polarization effect in Pb(Zr0.50Ti0.50)O-3 thin films with no preferential orientation - Lima, E. C. [UNESP]; Araujo, E. B. [UNESP]; Bdikin, I. K.; Kholkin, A. L. (Pergamon-Elsevier B.V. Ltd, 2012)
This work demonstrates the existence of a self-polarization effect in Pb(Zr0.50Ti0.50)O-3 thin films with no preferential orientation. Piezoresponse Force Microscopy (PFM) and dielectric measurements were used to study the origin of this effect. The presence of only one peak shifting slightly to the negative side in the piezoresponse histogram indicates the existence of a self-polarization effect in the studied films. An increase in self-polarization was observed when the film thickness increases from 200 nm to 710 nm. The results suggest that Schottky barriers and/or mechanical coupling near the film-electrode interface are not the main mechanisms responsible for the self-polarization effect in the studied films. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Thin films; Atomic force microscopy; Dielectric properties